Still lifes: the transformation of the everyday - Lopez, Wendy Kathleen, author; Dietemann, David L., advisor; Yust, Dave, 1939-, committee member; Coronel, Patricia D., committee member; Rock, Kenneth W., committee member (Colorado State University. Libraries, 1992)
What I find of particular interest is the transformation of the mundane. Through this series of still life paintings, I convey an acceptance of and love for everyday life -- life not characterized by memorable events, but by a sort of constant clutter that denotes human presence and communal living. I choose common objects (chairs, bowls, jewelry ... ) because of my emotional ties to the people they represent or their ability to access my memories. The result is an elevation of the ordinary to a place of value, through focused attention, rich coloration, sensuous textures, and exuberant brush stroke.
Keywords: still-life in painting